Anatomorphometry of the brachial plexus under high-definition system: an experimental study in rats - Rui Sergio Monteiro de Barros (Acta Cirúrgica Brasileira, 2022)
ABSTRACT Purpose: To study the anatomorphometry of the plexus brachialis (PB) of rats under a high-definition video system. Methods: Ten male Wistar rats discarded from other research that did not interfere in the morphology of the animal, respecting the principle of reduction, were used. All animals were submitted to the same protocol. Initially, the cervical region was shaved. The animals were placed in a dorsal position. A single elbow-to-elbow incision was performed and dissection started at the deltopectoral sulcus. The procedures were performed under a video system. To measure the structures, the Image J software was used. Results: All the PB evaluated originated from the C5-T1 spinal nerves. C5 and C6 converged to form the truncus superior, the root of C7 originated the truncus medius, and the confluence of C8 and T1 originated the truncus inferior. It was found the union of C7, C8, and T1 to form truncus inferomedialis instead of separate medial and inferior truncus. C8 (1.31 mm) was the thickest root, the truncus inferior (1.80 mm) and the nerve radialis (1.02 mm), were the thickest. Conclusions: The anatomy of the PB is comparable to humans, admitting variations. The videomagnification system is useful to perform microsurgical dissection.